H3ABioNet genomic medicine and microbiome data portals hackathon proceedings. (17th April 2021) - Fadlelmola, Faisal M; Ghedira, Kais; Hamdi, Yosr; Hanachi, Mariem; Radouani, Fouzia; Allali, Imane; Kiran, Anmol; Zass, Lyndon; Alsayed, Nihad; Fassatoui, Meriem; Samtal, Chaimae; Ahmed, Samah; et al.
Abstract: African genomic medicine and microbiome datasets are usually not well characterized in terms of their origin, making it difficult to find and extract data for specific African ethnic groups or even countries. The Pan-African H3Africa Bioinformatics Network (H3ABioNet) recognized the need for developing data portals for African genomic medicine and African microbiomes to address this and ran a hackathon to initiate their development. The two portals were designed and significant progress was made in their development during the hackathon. All the participants worked in a very synergistic and collaborative atmosphere in order to achieve the hackathon's goals. The participants were divided into content and technical teams and worked over a period of 6 days. In response to one of the survey questions of what the participants liked the most during the hackathon, 55% of the hackathon participants highlighted the familial and friendly atmosphere, the team work and the diversity of team members and their expertise. This paper describes the preparations for the portals hackathon and the interaction between the participants and reflects upon the lessons learned about its impact on successfully developing the two data portals as well as building scientific expertise of younger African researchers. Database URL : The code for developing the two portals was made publicly available in GitHub repositories: [https://github.com/codemeleon/Database ; https://github.com/codemeleon/AfricanMicrobiomePortal ].